Properties of an acrylic resin after immersion in antiseptic soaps: Low-cost, easy-access procedure for the prevention of denture stomatitis - de Oliveira Zoccolotti, Jacqueline [UNESP]; Tasso, Camilla Olga [UNESP]; Arbeláez, Maria Isabel Amaya [UNESP]; Malavolta, Isadora Ferreira [UNESP]; da Silva Pereira, Eduarda Carolina [UNESP]; Esteves, Caroline Stefanie Gomes [UNESP]; Jorge, Janaina Habib [UNESP] (Public Library of Science (PLoS), 2018)
Denture stomatitis triggered by Candida species requires better preventive measures. This study evaluated the physical and biological properties of a denture base acrylic resin after immersion in antiseptic soaps. Acrylic resin specimens were prepared and stored in distinct solutions for 0, 7, 14, 21, and 28 days. The solutions were as follows: DW: distilled water at 37C (control group); DS: cycles of daily immersion in Dettol soap for 8 hours at room temperature, followed by immersion in distilled water for 16 hours at 37C; PS: cycles of daily immersion in Protex soap, as described for the previous group; LS: cycles of daily immersion in Lifebuoy soap, as described for the DS group. The parameters evaluated at each time point were the following: biofilm formation capacity by Candida albicans and reduction of preformed fungal biofilms, cytotoxicity, surface roughness, hardness, and color change. For the fungal adhesion phase, the type of soap had a statistically significant effect (p = 0.0292), but after 24 hours, no differences were found between solutions or between storage times. Regarding the efficacy of biofilm reduction, there was a significant difference when the groups were compared to each other (p = 0.014). Dettol and Lifebuoy eliminated the preformed biofilm on the specimens. Moreover, all the soaps were classified as non-cytotoxic (on HaCaT cell line) because there was no difference in cell viability between the different groups, except after 21 days, when a decrease in cell viability occurred, regardless of the type of soap. Regarding the roughness, there was no statistically significant difference (p > 0.05) between the groups. Lifebuoy decreased resin hardness regardless of storage time (p = 0.003). After 21 and 28 days of storage, there was an increase in hardness value, regardless of the type of soap. The specimens’ color, according to the National Bureau of Standards values, ranged from 0.27 to 0.58 (i.e., imperceptible or mild color changes). In general, the disinfectant soaps were not able to prevent biofilm formation, but all the soaps were effective in reducing the preformed biofilm. In addition, all soaps were non-cytotoxic and did not change surface roughness, hardness (except Lifebuoy), and color (except Lifebuoy). Therefore, immersion in two antiseptic soaps (Protex and Dettol) may be a cheap and easy procedure for preventing denture stomatitis.